Endothelial-like malignant glioma cells in dynamic three dimensional culture identifies a role for VEGF and FGFR in a tumor-derived angiogenic response - Smith, Stuart J.; Ward, Jennifer H.; Tan, Christopher; Grundy, Richard G.; Rahman, Ruman (Impact Journals, 2015)
Aims: Recent studies have observed that cells from high-grade glial tumors are capable of assuming an endothelial phenotype and genotype, a process termed ‘vasculogenic mimicry’ (VM). Here we model and manipulate VM in dynamic 3-dimensional (3D) glioma cultures. Methods: The Rotary Cell Culture System (RCCS) was used to derive large macroscopic glioma aggregates, which were sectioned for immunohistochemistry and RNA extracted prior to angiogenic array-PCR. Results: A 3D cell culture induced microenvironment (containing only glial cells) is sufficient to promote expression of the endothelial markers CD105, CD31 and vWF in a proportion of glioma aggregates in vitro. Many pro-angiogenic genes were upregulated in glioma aggregates and in primary explants and glioma cells were capable of forming tubular-like 3D structures under endothelial-promoting conditions. Competitive inhibition of either vascular endothelial growth factor or fibroblast growth factor receptor was sufficient to impair VM and downregulate the tumor-derived angiogenic response, whilst impairing tumor cell derived tubule formation. Glioma xenografts using the same cells reveal tumor-derived vessel-like structures near necrotic areas, consistent with widespread tumor-derived endothelial expression in primary glioma tissue. Conclusions: Our findings support studies indicating that tumor-derived endothelial cells arise in gliomas and describe a dynamic 3D culture as a bona fide model to interrogate the molecular basis of this phenomenon in vitro. Resistance to current anti-angiogenic therapies and the contribution of tumor derived endothelial cells to such resistance are amenable to study using the RCCS.